BINGKAI MEDIA MENGENAI PEMBUNUHAN VINA OLEH GENG MOTOR DI CIREBON, JAWA BARAT (ANALISIS FRAMING ZHONGDANG PAN DAN GERALD M. KOSICKI PADA MEDIA ONLINE REPUBLIKA.CO.ID PERIODE 15 MEI – 15 AGUSTUS 2024) - Yudiansyah, Dafa Putra; Maserona, Lukas (Solidaritas, 2025)
An act can be said to be murder because the act results in the loss of someone's life by anyone intentionally. The murder case of Vina in Cirebon, West Java is one example of a murder case that went viral in 2024. This case occurred in 2016, but through the release of the film Vina: Sebelum 7 Hari, this case resurfaced in 2024. After the release of the film, the Vina murder case received attention from various online news portals, including Republika.co.id which is one of the best online news portals in Indonesia. The framing from Republika.co.id becomes interesting if analyzed in more depth, considering that in the process of this case there are still many pros and cons in society. Therefore, this study aims to determine the framing related to the news of the murder of Vina by a motorcycle gang in Cirebon, West Java. This study uses a qualitative method and is analyzed using the framing analysis theory of Zhongdang Pan and Gerald M. Kosicki with four analysis tools (Syntax, Script, Thematic, and Rhetoric). The conclusion of this study shows how Republika.co.id frames the Vina murder case by siding with the victim and Vina's family, and emphasizes the negative image of the police as an institutional figure who often commits injustice in the legal process. This is further confirmed by the way Republika.co.id media highlights the flaws in the legal process in Indonesia. Keywords: Framing Analysis, Republika.co.id, Vina, Murder